Associations of nadir haemoglobin level and red blood cell transfusion with mortality and length of stay in surgical specialties: a retrospective cohort study. (1st April 2019) - Trentino, K. M.; Leahy, M. F.; Sanfilippo, F. M.; Farmer, S. L.; Hofmann, A.; Mace, H.; Murray, K.
Summary: Few studies have investigated if, and how, red cell transfusion and anaemia interact. We analysed 60, 955 admissions to three metropolitan hospitals in Western Australia between 2008 and 2017 to determine whether the relationship between red cell transfusion and outcomes in surgical patients differed by lowest (nadir) level of haemoglobin. At levels above 100 g.l −1, in‐hospital, 30‐day and 1‐year mortality were higher with transfusion, the adjusted odds ratios (ORs) (95%CI) being 8.80 (4.43–17.45) p < 0.001 and 3.68 (1.93–7.02) p < 0.001 and the adjusted hazard ratio (95%CI) being 1.83 (1.28–2.61) p = 0.001, respectively. Likewise, between 90 g.l −1 and 99 g.l −1, in‐hospital, 30‐day and 1‐year mortality were higher with transfusion, the adjusted odds ratio (95%CI) being 3.76 (2.23–6.34) p < 0.001 and 1.96 (1.23–3.12) p < 0.001 and the adjusted hazard ratio (95%CI) being 1.34 (1.05–1.70) p = 0.017, respectively. Length of stay was longer with transfusion at nadir haemoglobin levels above 100 g.l −1 and in the following ranges: 90–99 g.l −1, 80–89 g.l −1, 70–79 g.l −1 and 60–69 g.l −1, the adjusted rate ratio (95%CI) being 1.38 (1.25–1.53) p < 0.001, 1.18 (1.10–1.27) p < 0.001, 1.17 (1.13–1.22) p < 0.001, 1.07 (1.02–1.12) p = 0.003 and 1.24 (1.13–1.36) p < 0.001, respectively. Mortality was higher with red cell transfusion at haemoglobin levels greater than 90 g.l −1, whereas at all levels below 90 g.l −1 mortality was not significantly higher or lower. Length of stay was longer with transfusion at nadir haemoglobin levels of 60 g.l −1 or above. Our results suggest that nadir haemoglobin modified the relationship between red cell transfusion and outcomes and adds to the evidence recommending caution before transfusing red cells. Abstract : 赤血球輸血と貧血との相互作用およびその機序についての研究は, ほとんど行われていない。本研究では, 2008 2017 年における西オーストラリア州の大都市病院3 施設の入院60, 955 件を分析し, 赤血球輸血と手術患者の転帰との関連性がヘモグロビン最低値によって異なるか否かを検討した。ヘモグロビン最低値が100 g.L–1 超の患者では, 院内死亡率, 30 日死亡率および1 年死亡率は輸血を実施した場合に高く, 調整オッズ比(OR)[95%信頼区間(CI)]は院内死亡について8.80(4.43 17.45)(p < 0.001), 30 日死亡について3.68(1.93 7.02)(p < 0.001)であり, 1 年死亡の調整ハザード比(95% CI)は1.83(1.28 2.61)(p = 0.001)であった。同様に, ヘモグロビン最低値が90 99 g.L–1 の患者では, 院内死亡率, 30 日死亡率および1 年死亡率は輸血を実施した場合に高く, 調整OR(95% CI)は院内死亡について3.76(2.23 6.34)(p < 0.001), 30 日死亡について1.96(1.23 3.12)(p < 0.001)であり, 1 年死亡の調整ハザード比(95% CI)は1.34(1.05 1.70)(p = 0.017)であった。入院期間は, ヘモグロビン最低値が100 g.L– 1 超, 90 99 g.L –1, 80 89 g.L –1, 70 79 g.L –1, 60 69 g.L –1 の患者では, 輸血を実施した場合により長く, 輸血を実施しなかった患者と比較した調整率比(95% CI)はそれぞれ1.38(1.25 1.53)(p < 0.001), 1.18(1.10 1.27)(p < 0.001), 1.17(1.13 1.22)(p < 0.001), 1.07(1.02 1.12)(p = 0.003), 1.24(1.13 1.36)(p < 0.001)であった。死亡率は, ヘモグロビン最低値が90 g.L –1 超の患者では輸血を実施した場合に高かったが, 90 g.L –1 未満の患者ではすべてのヘモグロビン値において, 輸血に伴って死亡率が有意に高くなったり, 低くなったりすることはなかった。入院期間は, ヘモグロビン最低値が60 g.L –1 以上の患者では輸血を実施した場合に長かった。本研究の結果から, へモグロビン最低値によって赤血球輸血と 転帰との関連性は変化することが示唆され, 赤血球輸血の前には十分な注意を払うことを推奨するエビデン スが新たに得られた。